Antispasmodic activity of the ethanol extract of Citrullus lanatus seeds: Justifying ethnomedicinal use in Pakistan to treat asthma and diarrhea. (15th September 2022) - Wahid, Muqeet; Saqib, Fatima; Qamar, Muhammad; Ziora, Zyta M.
Abstract: Ethnopharmacological relevance: Citrullus lanatus (Thunb.) belongs to the ground family, Cucurbitaceae, known for edible fruit. Besides nutritional benefits, the traditional herbal practitioners in Pakistan and India used their seeds to treat gastrointestinal, respiratory, and urinary disorders. In Northern Sudan, its seeds are often used as a laxative. Its root is laxative and emetic at a high dose. Its seeds are also used to treat bedwetting and urinary tract obstruction. Aim of the study: This study aimed to elucidate the multi-target mechanisms of Citrullus lanatus seeds to treat asthma and diarrhea. The pharmacological experiments were designed and conducted, along with the pharmacology network and molecular docking predictions, to verify the seeds biopotency for antispasmodic and bronchodilator properties. Methods: LC ESI-MS/MS were performed to identify the potentially active compounds in hydroethanolic extract of Citrullus lanatus seeds, then to quantify them by HPLC. The quantified bioactive compounds of Citrullus lanatus, i.e., stigmasterol, quinic acid, malic acid, epicatechin, caffeic acid, rutin, p-coumaric acid, quercetin, ferulic acid, scopoletin, apigenin, and kaempferol were subjected to in silico studies for molecular docking. The hydroethanolic extract of Citrullus lanatus seeds was examined on isolated rabbit tissue, i.e., jejunum, trachea, and urinary bladder. The antiperistalsis, antidiarrheal and antisecretory studies were also performed in animal models. Results: In silico studies revealed that bioactive compounds of C. lanatus seeds interfere with asthma and diarrhea-associated target genes, which are a member of calcium mediate signaling, regulation of cytosolic calcium concentration, smooth muscle contraction, and inflammatory responses. It was also found that rutin, quercetin, kaempferol, and scopoletin were stronger binding to voltage-gated calcium channels, calcium/calmodulin-dependent protein kinase, myosin light chain kinase, and phosphoinositide phospholipase C, thus, exerting calcium channel blocker activity. The hydroethanolic extract of C. lanatus seeds exerted a concentration-dependent relaxant response for the spasmolytic response on isolated jejunum and trachea preparations and caused relaxation of spastic contraction of K + (80 mM). Furthermore, it caused a non-parallel rightward shift with suppression of calcium concentration-response curves. In animal models, the Cl.EtOH showed antiperistalsis, antidiarrheal and antisecretory response. Conclusion: Thus, we confirm Citrullus lanatus seeds have some medicinal effects by regulating the contractile response through target proteins of calcium mediates signaling and can be a promising component in the medical treatment for asthma and diarrhea. Graphical abstract: Image 1